Proposta de índice de estado trófico em reservatórios do semiárido a partir de dados da bacia do Banabuiú, estado do Ceará - Rolim, Hosineide de Oliveira (2016)
The reservoirs built in the northeastern region are relatively shallow environments and large water mirrors, highly vulnerable to the dynamic action of the wind and the climatic oscillations. These environments tend to receive a high nutrient load and suspended sediment, since from their drainage area drains the waters of the concentrated rains in few months of the year, which favors erosive processes of the soil and makes them vulnerable to the phenomenon of eutrophication . In Ceará, specifically in the region of the Middle and Low Jaguaribe, it was found that most of the population does not have a public sewage system, with the use of septic tanks and wastewater being dumped in ditches and rivers, which contributes to the degradation Of the environmental quality of these reservoirs. The present work had as objective to develop a Trophic State Index that simulates the cumulative impact in 18 reservoirs of the Banabuiú basin, located in the semi - arid region of. Physical variables (temperature, transparency and turbidity), chemical (dissolved oxygen, pH and total phosphorus) and biological variables (chlorophyll a) were analyzed as indicators of the water quality of the reservoirs. The data used in this study were made available by the Water Resources Management Company of the State of Ceará (COGERH), in the years between 2010 and 2013. An adaptation to trophic classification (IETSA) was developed, incorporating the three most relevant variables for trophic evaluation Total Phosphorus, Chlorophyll a and Transparency. To interpret the data set, multivariate statistical techniques such as Hierarchical Grouping Analysis (AAH) and Factor Analysis / Principal Component Analysis (PCA) were used. The similarity of the reservoirs of the Banabuiú basin, in relation to the eutrophication of the waters, gave rise to three distinct groups, with groups I, II and III composed of nine, four and five reservoirs, respectively. From the calculation of the minimum and maximum values ​​and percentiles of the correlated parameters, four classes of trophic levels were established and it was observed that the reservoirs inserted in group I presented trophic classification predominantly between oligotrophic (54.7%), mesotrophic ( 30.2%), those of group II, eutrophic (44.4%) and hypereutrophic (33.3%) and group III, eutrophic (39.1%) and hypereutrophic (60.9%). The IETSA, presented a simple methodology and easy interpretation of the data, based on the water quality of the reservoirs located in the semi-arid region of Ceará. Therefore, its use may contribute to the reduction of errors in the inference of the trophic state of reservoirs in this region and should be seen as an indication for further studies.